Odpowiedzi

2010-04-08T19:46:49+02:00
A) 1/2x-3/4[x-(4x+1)]=1-x+1/4
1/2x-3/4[x-4x-1]=1-x+1/4
1/2x-3/4x-12/4x-1=1-x+1/4
1/2x-3/4x-3x-1=1-x+1/4
-1/4x-3x-1=1-x+1/4
-3i 1/4x -1=1-x+1/4
-3i 1/4x =1+1-x +1/4
2i 1/4x =2 i 1/4
x=1

B)2/3(3x - 1) - 3/2[2x + 3(x - 2)]=1
2/3(3x - 1) - 3/2[2x + 3x - 6]=1
2x-2/3 - 3x+9/2x - 9 =1
2x-3x+9/2x=1+9+2/3
7/2x=10i 2/3
7/2 x = 32/3
x=32/3 * 2/7
x=64/21
x=3 i 1/21

2010-04-08T20:50:39+02:00
A)1/2x-3/4[x-(4x +1)]= 1 - x+1/4
½ x - ¾ [x-4x-1] = 1- x + ¼
½ x - ¾ x + 3x + ¾ = 1- x + ¼
½ x - ¾ x + 3x + x = ¼ +1 - ¾
²/₄ x - ¾ x +4x = - ²/₄ +1
- ¼ x + 4x = ²/₄
3 ¾ x = ½
¹⁵/₄ x = ½ / * ⁴/₁₅
x = ²/₁₅

b) 2/3(3x - 1) - 3/2[2x + 3(x - 2)]=1
2x - ⅔ - ³/₂ [ 2x+ 3x-6] = 1
2x - ⅔ - 3x - ⁹/₂ x + 9 = 1
2x-3x - 4 ½ x = 1-9+ ⅔
-5 ½ x = -8 + ⅔
- ¹¹/₂ x = -7 ⅓
- ¹¹/₂ x = - ²²/₃ / * (-²/₁₁)
x = ⁴/₃
x = 1 ⅓